A case of eosinophilic pancreatitis in a patient with ulcerative colitis. Issue 2 (27th February 2023) - Toyoda, Koji; Katayama, Yasumi; Kobori, Ikuhiro; Kitahama, Akihiro; Kusano, Yumi; Ono, Yuko; Ban, Shinichi; Tamano, Masaya
ABSTRACT: Eosinophilic pancreatitis (EP) is very rare and characterised by infiltration of eosinophils into the pancreatic parenchyma. A 40-year-old man was diagnosed with total-colitis-type ulcerative colitis at the age of 15 years. He was then diagnosed with steroid-dependent ulcerative colitis. He was given golimumab, which resulted in remission. Ten months after beginning golimumab, he was urgently hospitalised with a diagnosis of acute pancreatitis. Hence, endoscopic ultrasound-guided fine needle biopsy was performed to obtain a definitive diagnosis. Pathologically, abundant infiltration of eosinophils was observed in the edematous intralobular stroma of the pancreas. He was diagnosed with EP, and treated with corticosteroids.